2016
DOI: 10.1242/dev.137489
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin activity in late hypertrophic chondrocytes locally orchestrates osteoblastogenesis and osteoclastogenesis

Abstract: Trabecular bone formation is the last step in endochondral ossification. This remodeling process of cartilage into bone involves blood vessel invasion and removal of hypertrophic chondrocytes (HTCs) by chondroclasts and osteoclasts. Periosteal- and chondrocyte-derived osteoprogenitors utilize the leftover mineralized HTC matrix as a scaffold for primary spongiosa formation. Here, we show genetically that β-catenin (encoded by Ctnnb1), a key component of the canonical Wnt pathway, orchestrates this remodeling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 78 publications
9
90
0
Order By: Relevance
“…Numerous genetic lineage tracing studies have demonstrated that chondrocytes directly contribute to endochondral bone formation by transforming into osteoblasts. 8,[12][13][14][15][16][17] This has been shown in the contexts of bone development, postnatal growth, and fracture repair with an array of reporter systems (Col10-Cre, Col2-Cre ERT2 , Aggrecan-Cre ERT2 , eGFP-and β-galactosidase-labelled tissue transplants). 8,[12][13][14][15][16][17] We advanced this here and show that chondrocytes are also likely precursors of progenitor cells that line the newly formed bone.…”
Section: Discussionmentioning
confidence: 92%
“…Numerous genetic lineage tracing studies have demonstrated that chondrocytes directly contribute to endochondral bone formation by transforming into osteoblasts. 8,[12][13][14][15][16][17] This has been shown in the contexts of bone development, postnatal growth, and fracture repair with an array of reporter systems (Col10-Cre, Col2-Cre ERT2 , Aggrecan-Cre ERT2 , eGFP-and β-galactosidase-labelled tissue transplants). 8,[12][13][14][15][16][17] We advanced this here and show that chondrocytes are also likely precursors of progenitor cells that line the newly formed bone.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, activation of Wnt signaling by stabilization of β‐catenin results in inhibition of preadipocyte differentiation into mature adipocytes via reducing PPARγ expression, raising the possibility that Wnt signaling determines the cell fate of osteoblastic and adipogenetic progenitors, priming them toward osteoblasts. Recent studies have provided in vivo evidence that removal of β‐catenin in the osteoblastic ( Osx‐Cre ) or chondrogenic ( Col10a1‐Cre ) lineages causes low bone mass and increased bone marrow adiposity . Although the HC origin of adipocytes in the Col10a1‐Cre ; β‐catenin conditional null mutants was not established, it is possible that a cell fate shift from the HCs‐derived osteoblasts into adipocytes may partly contribute to the observed phenotypes.…”
Section: Skeletal Lineage Plasticity In Development and Diseasementioning
confidence: 99%
“…Previous studies have demonstrated that the activation of the Wnt/β-catenin signaling pathway has a critical role in both osteoblastogenesis and osteoclastogenesis (4,5). In addition, aberrant activation of the Wnt/β-catenin signaling pathway has been shown to be involved in numerous types of cancers (6,7).…”
Section: Introductionmentioning
confidence: 99%